2022
DOI: 10.1002/bit.28052
|View full text |Cite
|
Sign up to set email alerts
|

Growth parameter estimation and model simulation for three industrially relevant microalgae: Picochlorum, Nannochloropsis, and Neochloris

Abstract: Multiple models have been developed in the field to simulate growth and product accumulation of microalgal cultures. These models heavily depend on the accurate estimation of growth parameters. In this paper growth parameters are presented for three industrially relevant microalgae species: Nannochloropsis sp., Neochloris oleoabundans, and Picochlorum sp. (BPE23). Dedicated growth experiments were done in photobioreactors to determine the maximal biomass yield on light and maintenance rate, while oxygen evolut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 34 publications
3
16
6
Order By: Relevance
“…Mut4 and mut11 displayed a maximal specific growth rate of 5.45 ± 0.23 d -1 and 5.71 ± 0.14 d -1 , respectively, which is significantly higher than the maximal specific growth rate of the wildtype, 3.35 ± 0.15 d -1 . The growth rate of the wildtype strain, grown on nitrate is comparable to values reported in previous research [157].…”
Section: Adaptive Laboratory Evolution Yields An Improved Mutant Strainsupporting
confidence: 88%
See 3 more Smart Citations
“…Mut4 and mut11 displayed a maximal specific growth rate of 5.45 ± 0.23 d -1 and 5.71 ± 0.14 d -1 , respectively, which is significantly higher than the maximal specific growth rate of the wildtype, 3.35 ± 0.15 d -1 . The growth rate of the wildtype strain, grown on nitrate is comparable to values reported in previous research [157].…”
Section: Adaptive Laboratory Evolution Yields An Improved Mutant Strainsupporting
confidence: 88%
“…Algaemist photobioreactors (Technical Development studio, WUR, The Netherlands) were used for characterization and comparison of growth characteristics and RNA expression patterns of the wildtype and two evolved strains of Picochlorum sp. BPE23 [157]. Cells were grown in turbidostat mode with similar growth conditions as in "paragraph 2.1.2.…”
Section: Characterization Of Mutant Strains -Photobioreactor Operationmentioning
confidence: 99%
See 2 more Smart Citations
“…Computational models are gaining attention with advanced software that may be employed for pathway prediction, data analysis, and optimization of bioproducts in microalgae cultivation [ 12 , 13 ]. Banerjee et al [ 12 ] showed the importance of computational modeling and prediction of microalgae growth focused on improved lipid production.…”
Section: Introductionmentioning
confidence: 99%